Estrogen matters : why taking hormones in menopause can improve and lengthen women's lives -- without raising the risk of breast cancer - Bluming, Avrum; Tavris, Carol (Little, Brown Spark, 2024)
"A compelling defense of hormone replacement therapy, exposing the faulty science behind its fall from prominence and giving women the evidence they need to make informed decisions about their health. Now fully revised and updated. For years, hormone replacement therapy (HRT) was the medically approved way to alleviate menopausal symptoms (ranging from hot flushes to brain fog) and reduce the risk of heart disease, Alzheimer's, and osteoporosis. But when a large study by the Women's Health Initiative (WHI) announced, with national fanfare, that women taking HRT had an increased risk of breast cancer, women were scared off, and the treatment was abandoned. Now, Dr. Bluming, a medical oncologist, and Dr. Tavris, a social psychologist, reveal the true story of the WHI's efforts to distort their data to exaggerate unsupported claims of estrogen's harms. Important updates in this edition include: Evidence that demolishes the WHI's claim that HRT causes breast cancer. A list of the WHI's retractions of their original scare stories. Updated findings on estrogen's benefits on heart, brain, bones, and longevity. A critical review of the alternative products and medications being marketed to treat symptoms of menopause. A sobering and revelatory read, Estrogen Matters sets the record straight on estrogen's benefits, providing a light to guide women through this inevitable phase of life."--Publisher.